2008
DOI: 10.1021/jp802762q
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of Rubrene on Copper Surfaces

Abstract: We report a detailed investigation of the self-assembly of the organic semiconductor rubrene on low-index (100) and (110) facets of copper by scanning tunneling microscopy (STM) and supported by density functional theory (DFT) calculations. Rubrene adsorbs in orientations depending on substrate symmetry, resulting in different self-assembled motifs. STM images point to an asymmetric adsorption geometry, and DFT calculations further suggest that the molecule adsorbs in a twisted conformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 67 publications
2
29
0
Order By: Relevance
“…9 This means that, in order to realize the crystallinity of rubrene molecules in monolayer regime, it requires additional energy ~205 meV to stabilize the planarization of twisted backbone of rubrene molecule. One may ask where this energy comes from?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 This means that, in order to realize the crystallinity of rubrene molecules in monolayer regime, it requires additional energy ~205 meV to stabilize the planarization of twisted backbone of rubrene molecule. One may ask where this energy comes from?…”
Section: Resultsmentioning
confidence: 99%
“…1(a), while the rubrene crystals adopt a planar tetracene backbone without any chirality. 9 Recently there has been tremendous effort in growing rubrene crystalline thin films on various substrates. Nevertheless, a lot of self-assembled monolayer (SAM) or supramolecular structures have been obtained on noble-metal substrates like Au, [10][11][12][13][14] …”
Section: Introductionmentioning
confidence: 99%
“…A Rub molecule can exist in two different structures known as twisted (D2) and planar (D1) isomers. The planar isomer is more stable in the crystal phase, since it favors the more dense packing of Rub molecules, while the twisted isomer is energetically more favorable for free molecules and those adsorbed on dielectric surfaces [11][12]. The chemical structure of Rub planar and twisted isomers and two possible geometrical isomers of Alq3, meridional (C1 symmetry) and facial (C3 symmetry) forms, are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The self-assembly of rubrene on pristine low index copper surfaces ((110) and (001)) will be discussed in more detail in a forthcoming paper. 51 Self-Assembly of Rubrene on the O-Cu Template. An STM image of the O-Cu nanotemplate used for this study is shown in Figure 3a.…”
Section: Self-assembly Of Rubrene On Pristine Cu(110)mentioning
confidence: 99%
“…Investigations on other Cu surfaces as well as density functional calculations are in progress to clarify this issue. 51 A tentative model for the adsorption geometry is illustrated in the upper portion of Figure 4a. The molecules assemble side by side into a tightly packed structure forming rows running in the same direction as the O-Cu stripes (i.e., the [001] direction of the pristine Cu surface).…”
Section: Self-assembly Of Rubrene On Pristine Cu(110)mentioning
confidence: 99%